Attitude and levels of awareness toward organ donation and transplantation among healthcare providers: A cross-sectional study - Hatan Mortada; Nawal Mashni Alharbi; Marya Abdullah Alsuhaibani; Rawan Abdullah Buhlagah; Yasmina Nezar Mohamed; Amjad Alharbi; Osama Y Safdar (Saudi Journal of Kidney Diseases and Transplantation, 2020)
End-stage organ damage is the major cause of death worldwide. The number of donors is low, and one of the challenging phases in organ donation is the availability of organ donors. There are many studies that suggest a strong correlation between knowledge and beliefs toward organ donation. A study conducted among Health-Care Providers in the Intensive Care Units at a Tertiary Center at Riyadh reported that only 57% of the health-care providers in the Intensive Care Unit were willing to donate their organs. The objective of our study was to evaluate the knowledge, attitude, and awareness of organ donation and transplantation among health-care providers at different hospitals around the Kingdom of Saudi Arabia. The data of this cross-sectional descriptive study were collected between February and July 2018 in different hospitals all around the Kingdom of Saudi Arabia. The investigators formulated a questionnaire based on several published studies. Ethical approval was obtained from the Unit of Biomedical Ethics, Research Committee at King Abdul Aziz University. Of the 241 participants, 130 (53.9%) were female. In addition, 110 (45.6%) of them were medical residents. Moreover, 224 (92.9%) participants were aware of the concept of organ donation. The overall level of knowledge is good (55.2%).The study showed 62.2% have participated in the organ donation program for their close relatives only. In conclusion, the level of perception and knowledge about organ donation among health-care providers was inadequate, although they showed positive attitudes toward this issue.